Health-related factors of psychological distress during the COVID-19 pandemic among non-health workers in Spain - Ruiz-Frutos, Carlos; Ortega-Moreno, Mónica; Allande-Cussó, Regina; Domínguez-Salas, Sara; Dias, Adriano [UNESP]; Gómez-Salgado, Juan (Elsevier, 2021)
Background: Non-health workers engaged in essential activities during the pandemic are less researched on the effects of COVID-19 than health workers. Objective: to study the differences between those who work away from home and those who do so from home, when the effects of fear of contagion cross with those of confinement, about the psychological distress during the COVID-19 in Spain. Design: Observational descriptive cross-sectional study. Data sources: The study was carried out receiving 1089 questionnaires from non-health workers that were working away from home and doing so from their homes. The questionnaire included sociodemographic and occupational data, physical symptoms, self-perceived health, use of preventive measures and possible contacts, and the Goldberg GHQ-12. Results: 71.6% of non-health female workers and 52.4% of non-health male workers had psychological distress, with differences among those working away from home and those working from home. The level of psychological distress among non-health workers is predicted by 66.5% through the variables: being a woman, 43 years old or younger, having a home with no outdoor spaces, poor perception of health, number of symptoms, and having been in contact with contaminated people or material. Among workers who work away from home, being self-employed is another predictive variable of distress. Conclusion: More than the half of the sample showed inadequate management of the psychological distress. There are modifiable factors which provide necessary elements to support a positive attitude of the workers, such as: knowledge of hygiene, transmission of the virus, protective measures, and social distancing measures.
Keywords: COVID-19; Mental health; Non-health workers; Pandemic; Psychological distress; Public health; Quarantine; Workers